RELATIONSHIP OF MUTATIONS TO CAREER DEVELOPMENT EMPLOYEE - Waloyo, Waloyo; Kurniawati, Rohmah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
This study aims to determine the relationship between mutations and career development. This research method uses descriptive method. The population in this study were 30 employees with a sample of 30 respondents, while the sampling technique used in this study was total sampling. Data collection techniques using a questionnaire using a Likert scale model. Data processing was carried out by a test drive of the questionnaire in order to determine the validity and reliability of the questionnaire. The data analysis technique in this study used simple linear regression analysis and correlation analysis. The results showed that there was a positive and significant effect of mutation on employee career development. The practical implication of this research is to measure the mutation variable that has an influence on career development, it turns out to have a significant influence between the two variables, the mutation variable makes a major contribution to the employee career development variable.